Outbreak of Klebsiella pneumoniae Carbapenemase–Producing Citrobacter freundii at a Tertiary Acute Care Facility in Miami, Florida. (7th December 2016) - Jiménez, Adriana; Castro, José G.; Munoz-Price, L. Silvia; de Pascale, Dennise; Shimose, Luis; Mustapha, Mustapha M.; Spychala, Caressa N.; Mettus, Roberta T.; Cooper, Vaughn S.; Doi, Yohei
Abstract : OBJECTIVE: To describe the investigation and control of a rare cluster of Klebsiella pneumoniae carbapenemase–producing Citrobacter freundii in a hospital in southern Florida. METHODS: An epidemiologic investigation, review of infection prevention procedures, and molecular studies including whole genome sequencing were conducted. RESULTS: An outbreak of K. pneumoniae carbapenemase–3-producing C. freundii was identified at a tertiary hospital in Florida in 2014. Of the 6 cases identified, 3 occurred in the same intensive care unit and were caused by the same clone. For 2 of the 3 remaining cases, the isolates had low carbapenem minimum inhibitory concentrations and were unrelated by whole genome sequencing. As a response to the outbreak, supplementary environmental cleaning was implemented, including closure and terminal cleaning of the unit where the 3 cases clustered, in addition to the infection control bundle already in place at the time. No further cases were identified after these additional interventions. CONCLUSIONS: Although C. freundii is not a species that commonly demonstrates carbapenem resistance, our findings suggest that carbapenemase-producing C. freundii may be underdetected even when active surveillance is in place and has a potential to cause hospital outbreak. Infect Control Hosp Epidemiol 2017;38:320–326